A Spinal Cord Stimulation Service Review From a Single Centre Using a Single Manufacturer Over a 7.5 Year Follow‐Up Period. Issue 6 (27th February 2017) - Thomson, Simon J.; Kruglov, Dmitry; Duarte, Rui V.
Abstract : Background: Spinal cord stimulation (SCS) is a recognized management option for patients with refractory neuropathic pain. Despite randomized controlled trials reporting the effectiveness of SCS, there is a lack of long‐term data reflecting usual SCS practice. The aim of this study is to present the long‐term outcomes of a cohort of patients from a single centre undertaking SCS with devices from a single manufacturer. Methods: Data were collected between January 2008 and July 2015 on 321 patients who had an SCS trial. Outcome measures included numerical rating scale of pain intensity (NRSPI), brief pain inventory (BPI), EQ5D and quality‐adjusted life‐years (QALYs). Adverse effects also were recorded. Results: Statistically significant reductions in NRSPI and BPI and increases in health utility using the EQ5d were observed. SCS over a 15‐year time period resulted in a mean projected gain of 6.2 QALY. The rates of implant infection and device explantation were 2.3% (2.4% not including legacy patients) and 6.7% (7.6% not including legacy patients) respectively but only 3.4% (4% excluding legacy patients) explanted due to late failure to relieve pain. Satisfaction with SCS was high with 92% of patients stating that they would have it all done again for the same result. 96.4% would have wanted SCS as a treatment option earlier. Conclusions: Patients with neuropathic pain undertaking SCS experience long‐term reductions in pain intensity and increases in health utility and associated QALY gains. The findings from this study associated with the increased longevity of rechargeable SCS devices suggest that the cost‐effectiveness of SCS may become increasingly favourable when compared with conventional medical management.